The effect of the APOE4 genotype on physiological and cognitive health in randomised controlled trials with an exercise intervention: a systematic review and meta-analysis - Felicity S. E. Spencer; Richard J. Elsworthy; Leigh Breen; Jon R. B. Bishop; Connor Dunleavy; Sarah Aldred (Trials)
Abstract Background Alzheimer’s disease is caused by modifiable and non-modifiable risk factors. Randomised controlled trials have investigated whether the strongest genetic risk factor for Alzheimer’s disease, APOE4, impacts the effectiveness of exercise on health. Systematic reviews are yet to evaluate the effect of exercise on physical and cognitive outcomes in APOE genotyped participants. A quality assessment of these randomised controlled trials is needed to understand the impact genotype has on the potential success of intervention. This systematic review aimed to determine if the APOE4 genotype influences the effectiveness of exercise-based randomised controlled trials. Method Searches on MEDLINE, EMBASE, and PsycINFO identified eligible exercise based randomised controlled trials incorporating participants with varied cognitive abilities. Quality assessments were conducted. Results Nineteen studies met the inclusion criteria for systematic review, and 3 for the meta-analysis. Very low to moderate quality evidence showed that APOE4 carriers benefitted more than APOE4 non-carriers on cognitive (e.g. executive function, learning) and physical (e.g. relative telomere length) outcomes after exercise; and that APOE4 non-carriers benefited over carriers for physical (serum BDNF, gait speed) and cognitive (global cognition, verbal memory) markers. Very low quality evidence indicated that there was no evidence of difference between APOE4 carriers and non-carriers on physical function outcomes in meta-analysis. Several areas of study design and reporting, including maintenance of relative exercise intensity and complete statistical reporting, were identified as needing improvement. Discussion This systematic review found very limited evidence to suggest that exercise interventions can benefit APOE4 carriers and non-carriers equally, though conclusions were limited by evidence quality. Further randomised controlled trials, stratifying participants by APOE status are required to better understand the relationship between APOE genotype and the effect of exercise on health-related outcomes. Trial registration This review was registered with PROSPERO (CRD42023436842). Registered on June 16, 2023.